2020
DOI: 10.1186/s13731-020-00127-3
|View full text |Cite
|
Sign up to set email alerts
|

Does government support enhance the relation between networking structure and sustainable competitive performance among SMEs?

Abstract: Purpose The underlining study’s main objective is to examine how networking structure (density and centrality) affects sustainable competitive performance in Pakistan’s SMEs. Design/methodology/approach Hence, small enterprises a significant source of economic development, employment, and value creation. Therefore, on the base of previous literature, we developed hypothesis related government financial support and network structure, and data collected through structured questionnaires from top management of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 64 publications
4
34
0
1
Order By: Relevance
“…The tax holiday, subsidized rate financing, financial incentives 5 Alkahtani et al [115]; Zamberi Ahmad and Xavier [116] Disagree 1 to strongly agree 5…”
Section: Government Supportmentioning
confidence: 99%
“…The tax holiday, subsidized rate financing, financial incentives 5 Alkahtani et al [115]; Zamberi Ahmad and Xavier [116] Disagree 1 to strongly agree 5…”
Section: Government Supportmentioning
confidence: 99%
“…However, the question is still elusive whether the tangible resources or intangible resources are more useful for a firm's success. Considering business firms in China and Pakistan, studies have reported a high failure ratio because of poor support, lack of managerial skills, and deficiency of resources (Alkahtani et al, 2020;S. Z. Khan, Yang, & Waheed, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This research contributes to the RBV theory (Barney, 1991) that states the prevalence of tangible and intangible resources in superior performance and SCA. However, RBV theory gives more weight to intangible resources over tangible means (Alkahtani et al, 2020;S. Z. Khan, Yang, & Waheed, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, policymakers should reconsider the current subsidy regime and ensure flexible and targeted financial incentives to support SMEs regarding the acquisition of new knowledge and skills (Groot et al 2019). According to Alkahtani et al (2020), a networking structure ensures governments' financial support (e.g., credit or tax incentives and subsidies). Therefore, an additional focus should be directed to local and international networking by local governments to boost the responsible and-at the same time-competitive performance of SMEs.…”
Section: Discussionmentioning
confidence: 99%